2020
DOI: 10.1007/s10439-020-02521-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Drug Effects on iPSC Cardiomyocytes with Machine Learning

Abstract: Patient-specific induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) offer an attractive experimental platform to investigate cardiac diseases and therapeutic outcome. In this study, iPSC-CMs were utilized to study their calcium transient signals and drug effects by means of machine learning, a central part of artificial intelligence. Drug effects were assessed in six iPSC-lines carrying different mutations causing catecholaminergic polymorphic ventricular tachycardia (CPVT), a highly malignant inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…As reviewed in great detail in this recent review article, 9 various classes of anti‐arrhythmic drugs with RyR2 inhibitory properties have been developed and some show great promise for the treatment of CPVT. Patient‐derived induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) offer a powerful cellular model to evaluate the potential effectiveness and safety of experimental drugs in a preclinical human cell model 22 . In the present study, we developed and characterized a novel iPSC‐CM cell line containing an N‐terminal variant R176Q in RyR2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed in great detail in this recent review article, 9 various classes of anti‐arrhythmic drugs with RyR2 inhibitory properties have been developed and some show great promise for the treatment of CPVT. Patient‐derived induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) offer a powerful cellular model to evaluate the potential effectiveness and safety of experimental drugs in a preclinical human cell model 22 . In the present study, we developed and characterized a novel iPSC‐CM cell line containing an N‐terminal variant R176Q in RyR2.…”
Section: Discussionmentioning
confidence: 99%
“…Patient‐derived induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) offer a powerful cellular model to evaluate the potential effectiveness and safety of experimental drugs in a preclinical human cell model. 22 In the present study, we developed and characterized a novel iPSC‐CM cell line containing an N‐terminal variant R176Q in RyR2. Our studies revealed evidence for abnormal diastolic SR Ca 2+ release events in spontaneously beating and paced single iPSC‐CMs containing the R176Q variant in RyR2.…”
Section: Discussionmentioning
confidence: 99%
“…The well-established role of iPSCs in disease modeling and AI in therapeutics has also been exploited in several studies. Juhola et al [ 173 ] used iPSC-derived cardiomyocytes to study drug effects and their calcium transient signals with ML. Six iPSC-lines containing various catecholaminergic polymorphic ventricular tachycardia causing mutations were used to assess the drug-effect.…”
Section: Recent Ai-based Models For Stem Cells Therapymentioning
confidence: 99%
“…Juhola et al used six cell lines of catecholaminergic polymorphic ventricular tachycardia (CPVT)-specific iPSC-cardiomyocytes that consisted of 128 calcium transient signals for each baseline, adrenaline, and dantrolene (a muscle relaxant drug) conditions. Three measurements were recorded from human iPSC cardiomyocytes' calcium transient data via the machine learning method [ 23 ]. First, transient signal beats were identified using the peak recognition algorithm, then 12 peak variables were computed for each identified peak of a signal, and using this data, signals were classified into different classes corresponding to those affected by adrenaline or, later by dantrolene which showed calcium abnormalities during adrenaline perfusion [ 23 ].…”
Section: Reviewmentioning
confidence: 99%